Super burp! - Krulik, Nancy E.; Blecha, Aaron (New York : Grosset & Dunlap, 2010)
When fourth-grader George starts at a new school, he vows to become a model student instead of the class clown he has always been, but just as his plan is going really well, he is overtaken by a magic burp that turns him back into a mischief-maker.
550
Accelerated Reader AR
Keywords: Conduct of life -- Juvenile fiction; Belching -- Juvenile fiction; Magic -- Juvenile fiction; Schools -- Juvenile fiction; Moving, Household -- Juvenile fiction; Behavior -- Fiction; Belching -- Fiction; Magic -- Fiction; Schools -- Fiction; Moving, Household -- Fiction